Immunodetection of Pectic Epitopes, Arabinogalactan Proteins, and Extensins in Mucilage Cells from the Ovules of Pilosella officinarum Vaill. and Taraxacum officinale Agg. (Asteraceae) - Płachno, Bartosz J. (Int J Mol Sci, 2020)
The main aim of this study was to compare the cytological difference between ovular mucilage cells in two Asteraceae species—Pilosella officinarum and Taraxacum officinale—in order to determine whether pectic epitopes, arabinogalactan proteins, or extensins are present. The immunocytochemical technique was used. Both the Taracacum and Pilosella genera have been used recently as models for understanding the mechanisms of apomixis. Knowledge of the presence of signal molecules (pectic epitopes, arabinogalactan proteins, and extensins) can help better understand the developmental processes in these plants during seed growth. The results showed that in Pilosella officinarum, there was an accumulation of pectins in the mucilage, including both weakly and highly esterified pectins, which was in contrast to the mucilage of Taraxacum officinale, which had low amounts of these pectins. However, Taraxacum protoplasts of mucilage cells were rich in weakly methyl-esterified pectins. While the mucilage contained arabinogalactan proteins in both of the studied species, the types of arabinogalactan proteins were different. In both of the studied species, extensins were recorded in the transmitting tissues. Arabinogalactan proteins as well as weakly and highly esterified pectins and extensins occurred in close proximity to calcium oxalate crystals in both Taraxacum and Pilosella cells.